Evaluasi Penyimpanan Vaksin Covid-19 di Gudang Farmasi Dinas Kesehatan Provinsi Jambi - Pratama, Septa (Program Studi Farmasi UNAJA, 2022)
Background: Vaccine management is a part of drug management cycle in the Office of Health, which is very important in all health services. Accurate and thorough vaccine management will positively impact the Ministry of Health interms of health, society and economy. Vaccines are very fragile and perishable biological products, so specialhandling is required in their management. Care should betaken to store vaccines in medical service units such as theHealth Department. This study aimed to determine theadequacy of vaccine storage at the Jambi provincial healthoffice in accordance with the 2015 guidelines for good drug distribution. Purpose: The purpose of this study was to test the vaccinestorage system at the Jambi Provincial Health Office.Methods: This study is a descriptive observational study. As astandard for comparison, the CDOB drug storage standard was used.Results: The results obtained were that the preservation ofvaccines in the pharmacy warehouse of the Jambi provincehealth department was 100% suitable for preservation, 100% daily maintenance, 83.3% monthly maintenance, 57.14 times installation and 100% match the building. Indicators.Conclusion: Based on the research results, it can beconcluded that the preservation of vaccines in the pharmacywarehouse of the Health Department of Jambi province iscorrect despite the shortcomings in facilities.